THE VALIDATION OF VALUES IN ECOLOGICAL ETHICS - Česlovas Kalenda (Problemos)
The making of modern ecological enthics, especially its development in the last quarter of the 20th century, is analysed in the article. Main attention is paid to the axialogical problem of how to validate the moral duty of the human being to protect nature: Is the reason for this duty the intrinsic value of nature or human needs and interests? The author suggests that the most theoretically interesting and promising standpoint is defended by A. Leopold, H. Rolston III, V. Hösle, and other investigators, who take as their point of departure the concept of the unity of nature and human beings. They hold that value concepts are an inherent part of the description of nature in scientific ecology. In this way the fatal opposition between fact and value is superseded. This standpoint opens up a new view of nature and expands the range of morally significant beings. These changes in ecological research and the constant rapid growth of ecological ethics during the last decades can apparently be considered as evidence that mankind feels an increasing need for new ecological humanism.